2005
DOI: 10.1080/10826080500260800
|View full text |Cite
|
Sign up to set email alerts
|

Dual Diagnosis and Quality of Life in Patients in Treatment for Opioid Dependence

Abstract: This study examined the relationship between quality of life (QOL) and dual diagnosis among patients in treatment for opioid dependence. The study sample includes 57 patients with opioid dependence alone (OD) and 41 with opioid dependence and a psychiatric axis-I disorder (DD), recruited in 2001 and 2004 at the Drug Addiction Services (SerT) of Bolzano and Pontedera (Italy). Participants were 73.5% males, with a mean age of 35.1 years (SD = 8.0). A comparison group of 45 healthy controls was also included. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 26 publications
13
71
1
Order By: Relevance
“…The researchers believe that physical health is influenced by psychological growth, and mental health promotion is based on the prevention and treatment of emotional stresses. Functioning in other domains of ProQOL is threatened as the level of mental health decreases (2).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers believe that physical health is influenced by psychological growth, and mental health promotion is based on the prevention and treatment of emotional stresses. Functioning in other domains of ProQOL is threatened as the level of mental health decreases (2).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the findings show that people improve their quality of life when they stop using non-prescribed opiates and undergo treatment with methadone (Padaiga, Subata, & Vanagas, 2007). However, when the results are compared between samples of people who are addicted to opiates and control samples, the scores have been systematically lower for the former and even more so with concurrent psychopathological diagnoses (Bizzarri et al, 2005).…”
Section: Introductionmentioning
confidence: 75%
“…The results of various studies indicate that the quality of life of addicts is lower than that of normal people [14]. Some studies have also shown that methadone and buprenorphine maintenance treatments have had positive effects on the life quality of the addicts [15].…”
Section: Introductionmentioning
confidence: 99%